INTERACTIVE METHODS IN ORGANIZING TUTORIAL СOURSES AND MODULES - Mukhammadjonova Madinabonu Isroiljon kizi (PT. Antis International Publisher, 2024)
This article provides information on the usage and preparation steps of interactive methods. These are the ones which is claimed as crucial in organizing tutorial classes. Absolutely, tutors should be knowledgeable in every phase of life and education in purpose of possessing their own reputation among students at the same time showing high impact on them. The one works as a tutor can improve working atmosphere and motivate his/her students to study